2021
DOI: 10.1016/j.heliyon.2021.e08030
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure chromatographic separation and UV/Vis spectrophotometric characterization of the native and desialylated human apo-transferrin

Abstract: Low-pressure pH gradient ion exchange separation provides a fast, simple and cost-effective method for preparative purification of native and desialylated apo-transferrin. The method enables easy monitoring of the extent of the desialylation reaction and also the efficient separation and purification of protein fractions after desialylation. The N -glycan analysis shows that the modified desialylation protocol successfully reduces the content of the sialylated fractions relative to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To quantify sialic acid content in native and desialylated AAG, the index of sialylation ( IS ) was used. The IS value was calculated using Equation (5): where n represents the number of N-glycan fractions, f i is the percentage of a specific N-glycan fraction of the total assigned N-glycans, and s i is the number of sialic acids present in the structure of each N-glycan fraction [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To quantify sialic acid content in native and desialylated AAG, the index of sialylation ( IS ) was used. The IS value was calculated using Equation (5): where n represents the number of N-glycan fractions, f i is the percentage of a specific N-glycan fraction of the total assigned N-glycans, and s i is the number of sialic acids present in the structure of each N-glycan fraction [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated that the absorbance of native human transferrin exhibits no significant dependence on changes in ionic strength up to 1.5 M [44].…”
Section: Molar Absorption Coefficient Of Native and Desialylated Aagmentioning
confidence: 93%
See 2 more Smart Citations
“…This coefficient was determined using the modied Edelhoch method, 44 and the result is consistent with previously published values (84.0 × 10 3 M −1 cm −1 and 84.8 × 10 3 M −1 cm −1 ). 45,46 The titration included 31 data points with separate preparations. In each case, an aliquot of FeNTA solution was added to a 0.1 mM human serum transferrin (hTf) solution.…”
Section: Binding Experiments With Human Serum Apo-transferrinmentioning
confidence: 99%